VISCOMETRIC BEHAVIOR OF CONCENTRTED PERCHLORIC ACID - Loshali, Renu; Kandpal, Narain Datt (Journal of the Chilean Chemical Society, 2017)
Viscosity ƞ and density ρ of aqueous concentrated perchloric acid 1.0moldm−3 to 9.0moldm−3 were measured at 297.65K. The viscosity data were used to calculate the value of A and B- coefficient of Jones- Dole equation. The value of B- coefficient is positive which suggests the strong ion- solvent interaction in aqueous perchloric acid. The three concentration regions of perchloric acid having value of B-coefficient (measure of ion-solvent interaction or structure making capacity) in the order 1.0 to 4.0moldm−3 < 4.0 to 6.0moldm−3 < 6.0 to 9.0moldm−3 has been proposed.